Peran PT. ITL Shipping Agency Dalam Mendukung Efisiensi Transportasi Laut Di Pelabuhan Adang Bay Tana Paser - sihombing, Benny sunardi; Mashartanto, Achmad Ali (Jurnal Cakrawala Bahari, 2025)
Maritime transportation plays a crucial role in supporting Indonesia’s national logistics system, as more than 90% of international trade activities rely on sea transport. Adang Bay Port, located in Tana Paser Regency, East Kalimantan, is one of the strategic ports serving as a major gateway for coal exports to international markets. This study aims to analyze the role of PT. ITL Shipping Agency as a shipping agency in improving maritime transport efficiency at Adang Bay Port. The research employed a descriptive qualitative approach supported by quantitative data, with information collected through interviews, observations, and documentation, as well as numerical analysis of vessel waiting times and operational costs. The findings reveal that ITL Shipping Agency contributes to three key aspects: (1) facilitating ship agency services, including permits and documentation; (2) enhancing operational efficiency in cargo handling and logistics; and (3) strengthening service quality through the adoption of digitalization. Data analysis indicates that the average vessel turnaround time decreased from 72 hours in 2019 to 62 hours in 2023, while operational costs were reduced by up to 16%. These results demonstrate that the presence of professional shipping agencies provides a tangible contribution to maritime transport efficiency. The study recommends strengthening digital-based agency services, diversifying shipping agency functions, and enhancing multi-stakeholder collaboration to improve competitiveness and sustainability at Adang Bay Port.